Sentra Kerajinan Tenun Songket Sumatera Di Pekanbaru Dengan Pendekatan Arsitektur Postmodern - Gladies Imanda Utami Rangkuty; Muhammad Rijal; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
As a Malay traditional craft, Sumatera Songket is known it’s high culture value. With varioud of pattern, the songket has a peculiarity interesting to tourists. Therefore a facility to accommodate songket is needed to conserve and to provide information to public, in order to let them to know and learn decorative of pattern and the process of making the songket. The facility is a center of craft industrial area which produce songket. With the Postmodern Architecture approach, the concept of this center is Khazanah Songket Melayu which is defined as a high value of the culture. Through the neo-vernacularism design method, it is applied on zoning, the massing, the landscaping, and facade. This production center area has applied Songket pattern arrangement, the landscape is in accordance to the mass. While the mass has designed with decorative pattern ornament. The pattern of mangosteen, and local decorative ornament are applied to building facade in neo-vernacularism design.Keywords: Songket, Malay, Neo-Vernacularism, Postmodern Architecture.